Application of Intense Pulsed Light in the Treatment of Dermatologic Disease: A Systematic Review. Issue 4 (4th February 2014) - Wat, Heidi; Wu, Douglas C.; Rao, Jaggi; Goldman, Mitchel P.
<x xml:space="preserve">Abstract</x> Background The Food and Drug Administration (FDA) has approved intense pulsed light (IPL) devices for the treatment of a variety of benign pigmentary and vascular lesions, but the range of disease amenable to IPL treatment continues to expand, and there are no evidence‐based clinical guidelines for its use in FDA‐approved and off‐label indications. Objective To provide evidence‐based recommendations to guide physicians in the application of IPL for the treatment of dermatologic disease. Evidence review A literature search of the CENTRAL (1991 to May 6, 2013), EMBASE (1974 to May 6, 2013), and MEDLINE in‐process and nonindexed citations and MEDLINE (1964 to present) databases was conducted. Studies that examined the role of IPL in primary dermatologic disease were identified, and multiple independent investigators extracted and synthesized data. Recommendations were based on the highest level of evidence available. Findings Level 1 evidence was found for the use of IPL for the treatment of melasma, acne vulgaris, and telangiectasia. Level 2 evidence was found for the treatment of lentiginous disease, rosacea, capillary malformations, actinic keratoses, and sebaceous gland hyperplasia. Level 3 or lower evidence was found for the treatment of poikiloderma of Civatte, venous malformations, infantile hemangioma, hypertrophic scars, superficial basal cell carcinoma, and Bowen's disease. Conclusions IPL is an effective treatment modality for a growing range of dermatologic disease and in some cases may represent a treatment of choice. It is typically well tolerated. Further high‐quality studies are required.